Opini Mahasiswa Pengguna Media Online Pada Kredibilitas Akurasi Portal Dakta.Com Ditinjau Dari Penyajian Berita - Sri Desti Purwatiningsih; M Syahriramdani; Michael Jibrael Rorong (Prodi Ilmu Komunikasi Universitas Putera Batam, 2022)
The evolution of uncontrolled journalism become attention by reason of frequently not putting the objectivity as priority. (The accuracy credibility of news presentation). The purpose of this research is to understand the opinions of students who use online media on accuracy credibility of Dakta.com portal reviewed from their news presentation. This research uses ABC of Attitude theory by D.W. Rajecki (Affective, Behavioral, Cognitif). The components used are only on C component (Cognition). This research also uses Non probability sampling (sampling jenuh) and quantitative approach with quantitative descriptive method. Result of the research presents major percentage of students’ opinions tendency is in the expectation dimension. Students hope that Dakta.com can improve the accuracy credibility of their news presentation and update the content momentarily.